Disentangling the Impact of Omnichannel Integration on Consumer Behavior in Integrated Sales Channels - Trenz, Manuel; Veit, Daniel J.; Tan, Chee-Wee (MIS Quarterly, 2020)
“Brick-and-mortar” retailers, when expanding their businesses to online channels, can either add a separate online channel or integrate channels to enhance service offerings. Although past studies on channel choice have yielded insights into factors affecting consumers’ channel preference, there is a dearth of research that sheds light on when and why massive investments into channel integration would be preferred over online optimizations. To this end, we construct and validate a theoretical model that posits omnichannel integration services for acquisition and recovery as predictors of consumers’ online channel preference through influencing their perceptions of convenience and risk. Our experimental study reveals how distinct configurations of cross-channel service offerings affect consumers’ channel evaluations and decisions, as well as how comple-mentarities from channel integration across transaction and post-transaction phases can prevail over pure online substitutes. Consequently, this study bridges diagnostic and prescriptive research streams on multichannel and omnichannel retail by attesting to channel integration as a viable channel differentiator. From a practical standpoint, we compare 12 distinct channel configurations with regard to consumers’ core evaluative criteria and highlight the value of omnichannel integration since efficiency improvements to the online channel can only serve as a partial substitute to channel integration.